A comprehensive and perspective view of oncoprotein SET in cancer. (10th May 2018) - Bayarkhangai, Buuvee; Noureldin, Suzan; Yu, Liting; Zhao, Na; Gu, Yaru; Xu, Hanmei; Guo, Changying
Abstract: SET is a multifunctional oncoprotein which is ubiquitously expressed in all kinds of cells. The SET protein participates in many cellular processes including cell cycle, cell migration, apoptosis, transcription, and DNA repair. Accumulating evidence demonstrates that the expression and activity of SET correlate with cancer occurrence, metastasis, and prognosis. Therefore, the SET protein is regarded as a potential target for cancer therapy and several inhibitors are being developed for clinical use. Herein, we comprehensively review the physiological and pathological functions of SET as well as its structure‐function relationship. Additionally, the regulatory mechanisms of SET at both transcriptional and posttranslational levels are also discussed. Abstract : The oncoprotein SET takes part in multiple cellular processes, such as cell cycle, cell migration, apoptosis, gene transcription and DNA repair. The overexpression of SET associates with risk and progression of cancer. Therefore, the expression and activity of SET are precisely regulated at both transcriptional and posttranslational levels. The antagonism of SET has shown significant anti‐cancer effect.